Pengaruh Pemilihan Palet Warna Dalam E-Book Terhadap Representasi Identitas Desa Bigaran, Borobudur - Amata Fami; Sri Yusrina; Athallah Yacob Asy'ari; Irma RG Barus (Lembaga Pengembangan Kinerja Dosen, 2024)
This study employs Charles Sanders Peirce's triadic semiotic theory analysis and utilizes quantitative regression analysis to investigate the impact of color palette selection in e-books on representing the identity of Bigaran Village in Borobudur. Involving 50 respondents with a valid and reliable questionnaire, the research establishes a significant relationship between color palette selection and the perception of the village's identity. With a correlation coefficient of 0.792 and a determination coefficient of 62.76%, the study indicates a robust contribution in understanding how colors influence users' perception of Bigaran Village's identity. In other words, the brown color palette is considered successful in representing the identity of Bigaran Village, serving as an effective representamen. The main findings reveal a positive and significant association between color palette selection in e-books and the representation of Bigaran Village's identity. Consequently, this research is expected to contribute to a better understanding of the role of color in representing village identity in e-books.